Perancangan Aplikasi Penghargaan dan Peningkatan Kinerja Karyawan pada POLSEK Sawah Besar Berbasis Java dengan Metode Simple Additive Weighting (SAW) - Ariyani, Lusi (Jurnal Informatika Universitas Pamulang, 2020)
The Indonesian National Police Institution has issued a policy of Chief of Police Regulation Number 16 of 2011 concerning the Civil Servant Performance Assessment System at the National Police with a Performance Management System. In Indonesia, which is competency-based, it is necessary to provide an assessment based on performance standards in an objective, transparent and accountable manner in order to encourage achievement, productivity, dedication and work loyalty. Performance appraisal is a process to measure employee work performance based on work standards that have been set for a certain period. These work standards can be made both qualitatively and quantitatively, one of which can use the SAW method. The definition of the SAW (Simple Additive Weighting) is a way or method to find the weighted sum of the performance ratings in a company or organization. The SAW (Simple Additive Weighting) method is a system used to identify and measure the performance of employees at the National Police so that it is aligned with the organization's vision and mission. The SAW (Simple Additive Weighting) method can be useful in the performance assessment system at the Polsek Sawah Besar because this method has a high level of assessment accuracy.